Presentation methodologies: an assessment for forensic signature analysis. Issue 5 (2nd September 2020) - Conlan, Xavier A.; Stevens, Shani J.; Found, Bryan; Sherman, Craig D.H.; Durdle, Annalisa
ABSTRACT: This study introduces a new methodology – the Line-Up method – for the presentation of signatures for forensic comparison. This method gives one approach to reduce the potential for contextual bias that is present using the traditional Target methodology. The findings of the research showed no significant difference in the number of inconclusive opinions, or level of accuracy, between the two presentation methods when used by the forensic handwriting examiners. However, lay participants made significantly fewer correct calls using the Line-Up method than the Target method. The findings reported here also show that forensic handwriting examiners exhibit greater levels of accuracy of authorship opinion utilizing the Line-Up method compared with lay participants. An investigation of the levels of inconclusive opinion using the Line-Up method found that forensic handwriting examiners were significantly more likely to offer an inconclusive opinion than lay participants (lay participants mean 21.3%; forensic handwriting examiners mean 56.3%). This study has established a baseline that will serve as the platform for longitudinal studies and is the first study to involve forensic experts from different countries. It will enable more globally collaborative studies to be undertaken.